THE ROLE OF COMMUNITY SOCIAL CARE (PPKM) MANAGEMENT IN IMPROVING COMMUNITY WELFARE IN SENGON SARI VILLAGE, AEK KUASAN DISTRICT, ASAHAN REGENCY: A QUALITATIVE STUDY - Pendi Santoso; Jhon Simon; Fandi Alfiansyah siregar; Budiman Purba (Universitas Dharmawangsa Medan, 2026)
Community welfare improvement in villages does not only depend on government policies but also requiresactive participation from society through community-based social initiatives. One such initiative is the AlIkhlas Community Social Care Management (PPKM) Program in Sengon Sari Village, Aek Kuasan District,Asahan Regency. This study aims to analyze the strategies of PPKM Al-Ikhlas in improving communitywelfare, identify supporting and inhibiting factors, and explain the contribution of PPKM Al-Ikhlas to socialand economic development. Using a qualitative descriptive approach, data were collected through interviews,observations, and documentation. The findings show that PPKM Al-Ikhlas applies participatory strategies,deliberation, and direct services to the community. Supporting factors include strong social solidarity and trust,while inhibiting factors involve limited financial resources and uneven participation. The program contributespositively to fulfilling basic needs and strengthening social solidarity, complementing the role of villagegovernment in welfare improvement.Keywords: Community Welfare, PPKM, Social Solidarity, Village Development